2011
DOI: 10.1002/pca.1374
|View full text |Cite
|
Sign up to set email alerts
|

LC‐UV Assay Method and UPLC/Q‐TOF‐MS Characterisation of Saponins from Ilex Paraguariensis A. St. Hil. (Mate) Unripe Fruits

Abstract: The validated LC-UV method was shown to be linear, precise, accurate and to cover several saponins previously isolated from Ilex species and could be applied for the quality control of unripe fruit saponins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…The relatively high level of these enzymes secreted by the liver on the administration of both extracts calls for great caution in their indiscriminate administration. The increased ALT and AST obtained in this study was corroborated by [20].…”
Section: Alanine Aspartate Transferase (Ast)supporting
confidence: 82%
“…The relatively high level of these enzymes secreted by the liver on the administration of both extracts calls for great caution in their indiscriminate administration. The increased ALT and AST obtained in this study was corroborated by [20].…”
Section: Alanine Aspartate Transferase (Ast)supporting
confidence: 82%
“…The mate saponin enriched fraction was obtained through solid‐phase extraction, a process commonly used for saponins purification. The process showed a good reproducibility 30. LC–MS chemical fingerprint showed that all peaks presented molecular weights compatible with saponins and confirmed the presence of the chemical marker of MSF, ilexoside II 30.…”
Section: Resultsmentioning
confidence: 74%
“…The process showed a good reproducibility 30. LC–MS chemical fingerprint showed that all peaks presented molecular weights compatible with saponins and confirmed the presence of the chemical marker of MSF, ilexoside II 30. The zeta potential of the MSF solution was measured as −22.3 ± 1.4 mV.…”
Section: Resultsmentioning
confidence: 77%
“…Given the complexity of chemicals in herbal medicines, the pharmacokinetic profile of one major active ingredient will possibly be altered by coexisting components in the herbal extract [21,22]. Several methods for determining the presence of PDC in the genus Ilex and other herbal materials have used high-speed counter-current chromatography [23], high-performance liquid chromatography coupled with ultraviolet detection (HPLC-UV) [24,25], HPLC coupled with evaporative light scattering detection [26,27], and ultra-performance liquid chromatography/quadrupole time-of-flight mass spectrometry (UPLC/Q-TOF-MS) [28]. However, analysis of PDC in vivo has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%